Vaccination of patients with diabetes mellitus--a retrospective study - Mad'ar, Rastislav; Benesová, Dagmar; Brandejská, Dana; Cermáková, Miriam; Dvorková, Alena; Gazárková, Olga; Jakubalová, Silvana; Kochová, Ilona; Lastovicková, Jana; Nebáznivá, Dagmar; Orolinová, Marta; Polomis, Karel; et al. (Central European journal of public health, 2011)
402 subjects with diabetes mellitus have been vaccinated of the total of 34,000 vaccinees immunized during the study period of 9 and half months. Altogether 229 diabetic patients (56.97%) have been vaccinated'against tick-borne encephalitis (TBE) and 74 (18.4%) against viral hepatitis (41 types A+B, 30 type A, 3 type B). The average age in four most commonly administered vaccines (FSME IMMUN 0.5 ML, Twinrix Adult, Typhim Vi, and Havrix 1440) was 65, 52, 56, and 54 years, respectively. Live attenuated vaccines have been given to 6 patients with diabetes (1.49%)--- 5 travellers to endemic countries received the yellow fever vaccine Stamaril (1 female, 4 male) and one male patient varicella vaccine Varilrix. Among the least common vaccines in diabetic patients were those against invasive pneumococcal and meningococcal infections. Not a single unexpected side effect has been observed following the vaccination procedure in any diabetic patient. Based on the results of this retrospective study we can conclude that vaccination in diabetic patients is free of any ri-k- provided that there are no other contraindications, e.g. allergy to vaccine components or severe acute febrile illness. In the case of unstable glycaemia and significantly impaired immune system due to diabetes mellitus, vaccination with live attenuated vaccines should be carefully considered and measured against the risks of exposure to each and every specific infectious agent. There is no reason to be afraid of vaccination in diabetic patients provided that general contraindications are respected. On the contrary, this risk group can benefit from vaccination more remarkably since it may have some life-saving potential.
Keywords: senioři; Vaccines, Attenuated; senioři nad 80 let; Retrospective Studies; diabetes mellitus; mladiství; Česká republika; Encephalitis, Tick-Borne; Middle Aged; Diabetes Mellitus; mužské pohlaví; Vaccination; vakcinace; Adult; mladý dospělý; Czech Republic; dítě; Child; klíšťová encefalitida; Aged, 80 and over; Viral Vaccines; virové vakcíny; Young Adult; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; atenuované vakcíny; dospělí; nežádoucí účinky léčiv; Drug-Related Side Effects and Adverse Reactions; Aged; Female; Adolescent; lidé; Male